PENERAPAN ELECTRONIC FLIGHT PROGRESS STRIP DALAM KINERJA AIR TRAFFIC CONTROLLER DI PERUM LPPNPI KANTOR CABANG KUPANG - Fadhillah Yauma Ihsan Baidhowi; Wasito Utomo; Siti Nurfadhilah (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Paper Flight Progress Strip is a small piece of paper where an Air Traffic Controller records important data obtained from the pilot during the flight. Important data recorded in FPS paper include: callsign, aircraft type, from / purpose, height of roaming and other important data. Along with the advancement of technology, electronic flight progress strip / e-strip appears appears to replace the Paper Strip position. Perum LPPNPI Kantor Cabang Kupang is one of the airports used as an e-strip application. The e-strip system is currently operated through a computer and accessed via Google Chrome this causes the e-strip system to still have to be reset within a certain period of time to avoid longer loading computer and internet networks. The absence of legality and regulation related to e-strips makes the e-strip can not be used formally so that the Loca (Letter of Operational Coordination Agreement) e-strip cannot also be made. The application of e-strip is found on the International Civil Aviation Organization (ICAO) recommendation in the Asia Pacific Seamless ATM Plan document V2.0 2016 Chapter 5 points 73, "Switching from paper to electronics connected to the FDPS system or directly inputting data to ASD supports changes this. The use of the Flight Progress Strip paper can increase transcript errors / data mismatches. " The research method used by the author is descriptive qualitative The study concluded that there was a positive relationship between Electronic Flight Progress Strip (e-strip) in the performance of the water traffic controller coefficient of determination of 55%, meaning that the electronic flight progress strip optimization (e-strip) in the performance of the Air Traffic Controller Perum LPPNPI Kantor Cabang Kupang It is 55 %% and the remaining 45% are determined by other factors in this case not researched by the author.